(untitled) (Journal of Namibian Studies : History Politics Culture, 2022)
This study compares the training, education, and certification requirements for paramedics and nurses, two essential healthcare professions with distinct roles and responsibilities. Paramedics specialize in emergency medical care, undergoing intensive programs covering topics such as anatomy, pharmacology, and trauma management. They typically complete certificate or associate degree programs and must obtain certification through exams like the National Registry of Emergency Medical Technicians (NREMT). Nurses, on the other hand, provide comprehensive healthcare services across various settings, requiring either an associate degree or bachelor’s degree in nursing and licensure through exams like the National Council Licensure Examination for Registered Nurses (NCLEX-RN). Both professions emphasize clinical experience and continuing education to maintain competence. Understanding these differences is crucial for healthcare workforce planning and ensuring optimal patient care delivery.